The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/ac902944k
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Resonance Analysis of Antibiotics Using Imprinted Boronic Acid-Functionalized Au Nanoparticle Composites

Abstract: Au nanoparticles (NPs) are functionalized with thioaniline electropolymerizable groups and (mercaptophenyl)boronic acid. The antibiotic substrates neomycin (NE), kanamycin (KA), and streptomycin (ST) include vicinal diol functionalities and, thus, bind to the boronic acid ligands. The electropolymerization of the functionalized Au NPs in the presence of NE, KA, or ST onto Au surfaces yields bisaniline-cross-linked Au NP composites that, after removal of the ligated antibiotics, provide molecularly imprinted ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(75 citation statements)
references
References 45 publications
0
74
0
1
Order By: Relevance
“…Generally, SPR spectroscopy measures the optical dielectric constants of thin films deposited onto noble metal-coated substrates like Au NPs or Ag NPs, which are extremely sensitive to the refractive index changes occurring within a few hundred nanometers from the sensor surface. Moreover, the SPR sensors incorporated with MIPs have been widely used to monitor protein, 623 environmental contaminants, 624 drugs 625 and food. 626 In general, the combination of SPR with electrochemistry or applying the surface-initiated ATRP for grafting polymeric films on the Au chips is a powerful analytical technique.…”
mentioning
confidence: 99%
“…Generally, SPR spectroscopy measures the optical dielectric constants of thin films deposited onto noble metal-coated substrates like Au NPs or Ag NPs, which are extremely sensitive to the refractive index changes occurring within a few hundred nanometers from the sensor surface. Moreover, the SPR sensors incorporated with MIPs have been widely used to monitor protein, 623 environmental contaminants, 624 drugs 625 and food. 626 In general, the combination of SPR with electrochemistry or applying the surface-initiated ATRP for grafting polymeric films on the Au chips is a powerful analytical technique.…”
mentioning
confidence: 99%
“…Complementary approaches for tailoring the analytical performance of MIP architectures comprise the integration of nanomaterials such as metallic nanoparticles [3], carbon nanotubes [67], quantum dots [30] and graphene [68]. Synergistic combination of the different approaches may make the MIPs to real competitors of proteins and aptamers and open up the route to new fields of applications [69].…”
Section: Discussionmentioning
confidence: 99%
“…Frasconi et al [142] reported a novel surface-plasmon resonance (SPR) method for detection in milk of three antibiotics having vicinal diol functionalities (neomycin, kanamycin, and streptomycin). A special ''MIP'' for the analytes was prepared by electropolymerizing the AuNPs functionalized with thioaniline groups and (mercaptophenyl)boronic acid.…”
Section: Other Techniquesmentioning
confidence: 99%